IMPROVING THE LOGIN AND NEWS FEATURES WITH FINGERPRINT AND CARD LAYOUT: AN EVALUATION OF CONVERSION RATE AND USABILITY - Yogastama, Reyhan Ardiya; Kharisma, Agi Putra; Santoso, Nurudin (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2024)
The discipline of human factors or also known as ergonomics focuses on interactions between humans and artifacts. One example of such an artifact is a smartphone. Currently, many smartphones are equipped with various sensors, one example is the fingerprint sensor. Fingerprint sensors offer various conveniences, an example of their use is to simplify the login process. This research uses the Gapura UB application as a case study. Currently the Gapura UB application does not yet implement fingerprint login, so it is not yet known whether Gapura UB users will prefer to log in using the conventional method (email and password) or using a fingerprint. Apart from that, this research also investigated the usability of news features of Gapura UB when implementing a card layout (as a treatment) compared to the original version which uses a list layout (as a control). To answer these research problems, this research uses an experimentation with the research subjects from the students of Teknik Informatika, FILKOM UB and the research objects are conversion rate and usability. The conversion rate measurement involved 30 unmoderated participants, whereas the usability measurement involved 10 moderated within group participants. The results obtained on the fingerprint login conversion rate show that most participants prefer to use fingerprint login (73% ± 17%) rather than conventional login methods. Meanwhile, the results of the usability test on the news feature using the card layout showed that there was an increase in retention time (51 ± 15 seconds) compared to the original version which used the list layout (31 ± 14 seconds). The score of measurements using the system usability scale also show an increase in the card layout (90 ± 5) compared to the list layout (65 ± 15).